Prescription Pattern and Off-Label Use of Antipsychotics in a Middle Eastern Population - Bastaki, Kholoud; El Anbari, Mohammed; Ghuloum, Suhaila; Jithesh, Puthen Veettil (Frontiers in Pharmacology, 2021)
Background: Understanding the prescription pattern of medications in a population can help reveal the potential usage scenarios, including off-label prescriptions, and the need for precision medicine implementation. Therefore, the aim of this study was to assess the prescription pattern and off-label use of antipsychotics in the Qatari population. Methods: We performed a cross-sectional study of Qatari patients who received antipsychotic prescriptions from the major healthcare providers in the country during the 2-year period between June 2018 and May 2020. The number of patients, prescriptions dispensed, and clinical indications were collected and statistical analysis using chi-square test was conducted. Results: Among the 9,349 Qatari patients prescribed with antipsychotics during the study period, the majority were female (57%; p < 0.001) and were in the age categories 20–39 and 30–39 years (both 22%; p < 0.001). Among the 35,938 antipsychotic prescriptions dispensed, second-generation antipsychotics were the most highly prescribed (59%), specifically, quetiapine (16%) and olanzapine (12%), but the first-generation antipsychotic prochlorperazine (13%) was also highly prescribed. Most of the indications of antipsychotics (69%) were for off-label use such as for controlling chronic diseases, sleeping disorders, benign paroxysmal positional vertigo and irritable bowel syndrome. Conclusion: Non-mental health and off-label prescriptions of several antipsychotics were observed. Integration of this data with pharmacogenomic and clinical outcome data will help in determining the course of action for implementing personalized and precision medicine in the country and beyond.